2018
DOI: 10.4314/tjpr.v17i3.22
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of capecitabine and tegafur/gimeracil/oteracil (S-1) in the treatment of advanced breast carcinoma in the elderly

Abstract: Purpose: To analyse and compare the clinical effects and safety of capecitabine and tegafur/gimeracil/oteracil (S-1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Prior clinical studies have suggested that 5-FU prodrugs containing dihydropyrimidine dehydrogenase inhibitors such as S-1 or uracil/tegafur can reduce the incidence of HFS[17]. In this study, HFS was significantly less common in the S-1 group than in the capecitabine group, consistent with previous studies[18,19]. Although HFS is not life-threatening, it can significantly impair a patient’s daily activities and decrease their quality of life.…”
Section: Discussionsupporting
confidence: 90%
“…Prior clinical studies have suggested that 5-FU prodrugs containing dihydropyrimidine dehydrogenase inhibitors such as S-1 or uracil/tegafur can reduce the incidence of HFS[17]. In this study, HFS was significantly less common in the S-1 group than in the capecitabine group, consistent with previous studies[18,19]. Although HFS is not life-threatening, it can significantly impair a patient’s daily activities and decrease their quality of life.…”
Section: Discussionsupporting
confidence: 90%